Pattern of substance abuse among patients in a rehabilitation center - SangeethaLakshmi GNS,; Sowmini K,; Geervani Arige,; Bharathi Uppu, (Asian Journal of Medical Sciences, 2024)
Background: Substance use disorders have profound implications for individuals, their families, and society as a whole. At present, drug trafficking and addiction have ensnared every corner of the globe, impacting millions of individuals worldwide. This pressing issue of drug abuse is concerning due to the underlying conditions fueling it, including shifting cultural values, increasing economic stress, and weakened social support networks. Aims and Objectives: This study aimed to identify the trends in drug abuse and its influencing factors among patients undergoing treatment for addiction in rehabilitation centers in Telangana. Materials and Methods: The study, a descriptive cross-sectional analysis, involved 222 individuals grappling with drug addiction at the primary rehabilitation center for drug addiction treatment in Telangana. Information was gathered using a pre-tested, structured questionnaire between September and December 2022 under the Department of Pharmacology. Results: Among the respondents, 95% were male and 5% were female, with a majority falling in the 21–30 age brackets. The religious breakdown comprised 151 Hindus, 32 Muslims, and 30 Christians, while 41% hailed from tribal regions. Injection emerged as the most prevalent method of substance abuse among 194 participants. The onset of drug abuse mostly occurred between ages 11 and 20, primarily driven by self or peer pressure. Notably, 89% of participants reported being compelled to consume substances. Conclusion: The study found a significant correlation between male gender and drug consumption (P<0.05), as well as between the 21 and 30 age group and drug intake (P<0.05). Additionally, the research highlighted a high prevalence of drug dependence among educated individuals, with familial conflicts and peer pressure being cited as common triggers for various forms of substance abuse.